Effects of a lower limb muscular fatigue on posture–movement interaction during a lower limb pointing task - Silva, Marcelo Guimarães [UNESP]; Struber, Lucas; Daniel, Olivier; Nougier, Vincent (Springer Nature, 2021)
Purpose: The aim of the present study was to investigate the effects of muscular fatigue on the interaction between posture and movement during a lower limb pointing task. Methods: Participants (n = 16), aged 18–30 years, kicked a ball toward a target in four conditions of fatigue: No muscular fatigue (NF), fatigue in the kicking (FM) or postural limb (FP) alone, and fatigue in both limbs (FMP). The mean amplitude and speed of the centre of foot pressure (CoP) and centre of mass (CoM) displacements were estimated through a force platform and an optoelectronic system, respectively. In addition, surface electromyography (EMG) of the biceps femoris, rectus femoris, medial gastrocnemius, and peroneus longus was recorded to investigate the anticipatory postural adjustments (APAs). Results: Muscular fatigue yielded a decreased kicking accuracy (p < 0.001) and an increased time to perform the movement (p < 0.001), mainly during the backswing motion. In addition, significant increases in the mean amplitude and speed of the CoP and CoM displacement were found in the anteroposterior (AP) and mediolateral (ML) axes (ps < 0.001), especially when both limbs were fatigued. The EMG analysis confirmed that fatigue modified the way APAs were generated. During fatigue, postural muscle activity increased, but was delayed with respect to movement onset (ps < 0.001). This pattern of response was more consistent when both limbs were fatigued (p < 0.001). Conclusion: The present results suggested an additive effect of fatigue and a functional adaptation and subsequent decrease in the overall variability of APAs, indicating that postural and motor processes are interdependent.
Keywords: Anticipatory postural adjustments; Kicking accuracy; Muscular fatigue; Posture–movement interaction